Kidney failure treatment centers in Dhi Qar GovernorateAnd its future prospects by adopting forecasting models - Dr. Sami Jalab Mansi; Assis.Lectu. Hala Salim Yaqoub (Journal of College of Education, 2025)
The research aims to develop an applied study whose results can be used in the process of planning and evaluating the health services sector to serve the population of Dhi Qar Governorate in general to improve the provision of health services for kidney failure in Dhi Qar Governorate, according to projections or predicting the incidence rate according to prediction equations for regression models. The research adopted a questionnaire consisting of (265) questionnaires based on the (SPSS) program. The research concluded that the outcomes of the (general) quantitative analysis are that the general trend of the phenomenon under investigation in relation to the respondents’ response is the second level (compatibility Through building regression models, it was proven that the dependent variables (the number of patients receiving treatment in dialysis units for renal failure, the presence of crowding during treatment in dialysis units for renal failure, and the duration of treatment during the morning period) were significantly associated with the independent variables arranged by objective indicators followed by indicators that bear the identity of Population, which means forming predictive equations and models that can be relied upon in studying reality and future prospects that embody the picture of this chronic disease
Keywords: kidney failure, indicator, specialized centers, Likert scale, regression models